Noticeable improvement in morphological characteristics and thermal reliability of n-octadecane@SiO2 nanocapsules for thermal energy storage - Kim, Yuhyeok; Jo, Byeongnam (International Journal of Energy Research, 2022)
This study aims to examine a wide range of synthesis parameters to improve the morphological characteristic and the thermal reliability of nanoencapsulated n-octadecane via interfacial hydrolysis and polycondensation of tetraethyl orthosilicate (TEOS) in an oil in water (O/W) emulsion for thermal energy storage (TES). Various synthesis parameters, such as the surfactant, catalyst, solvent, and n-octadecane/ TEOS mass ratio were explored to determine the optimal conditions for the n-octadecane@SiO2 nanocapsules. First, the nanocapsules were placed on a hotplate at 80°C for 1 hour to visually check the leakage of the core (n-octadecane). No leakage was observed in the samples. The scanning electron microscopy analysis confirmed that the nanocapsules synthesized under optimal conditions existed individually without any clustering. The chemical composition and crystal structural characterization, as well as the morphological analysis, were also performed using an FTIR spectrometer and X-ray diffractometer. Moreover, the thermal performance of the synthesized nanocapsules was examined by measuring the melting enthalpy and estimating the encapsulation ratio (ER) using differential scanning calorimetry. The enthalpy and ER of the optimal sample were 119.8 J/g and 54.0%, respectively. Finally, the thermal reliability of the n-octadecane@SiO2 nanocapsules was analyzed by comparing the thermal performance before and after 100 heating and cooling cycles. After the repeated cycles, the encapsulation rate and efficiency of the synthesized nanocapsules exhibited a small variation of <1% compared to the initial values. The TES capacity of the n-octadecane@SiO2 nanocapsules between 20 and 40°C was estimated to be 134 MJ/m3, which is 59.5% larger than that of water. Based on the measurements and characterization, the n-octadecane@SiO2 nanocapsules synthesized under optimized conditions exhibited an outstanding thermal performance and thermal reliability; thus, it is highly useful for TES systems to harness solar or geothermal energy.
Keywords: Morphological characteristic; N-octadecane; Nano-encapsulation; Sol'gel; Synthesis parameters; Synthesised; Tetraethyl orthosilicates; Thermal energy storage; Thermal Performance; Thermal reliability; nanoencapsulation; phase change material; sol-gel; thermal energy storage; thermal reliability